Lactate/Albumin Ratio as a Predictor of Mortality in Patients with Sepsis and Septic Shock: A Meta-Analysis Study - Baihaqi, Fahri Ahmad; Delarosa, Dinda Olinda; Ramadhan, Rezki (UI Scholars Hub, 2022)
Introduction. The lactate/albumin ratio is an inflammatory biomarker that has been widely used and suggested as a predictor of mortality in patients with sepsis and septic shock. However, the results are inconsistent. This meta-analysis aimed to evaluate the prognostic value of lactate/albumin ratio as a predictor of mortality in patients with sepsis and septic shock.Methods. The study protocol was registered with PROSPERO (CRD42021286242). A literature search was performed using PubMed, Ovid EMBASE, Ovid MEDLINE, SCOPUS, and Web of Sciences to find all studies evaluating the association between lactate/albumin ratio and mortality in patients with sepsis and septic shock. Meta-analysis was performed to synthesize the overall Standardized Mean Difference (SMD) of the lactate/albumin ratio and the pooled Odds Ratio (OR) for mortality with 95% confidence intervals (95% CI). Heterogeneity was assessed using I2. Publication bias was assessed quantitatively with Egger’s test. Analysis was performed using Stata version 16.Results. Seven studies (n=10,264 patients) were included in the meta-analysis. The meta-analysis results showed that non-survivor had a higher lactate/albumin ratio than survivor (random-effects model; SMD 1.47; 95% CI 0,91-2,04; p <0.001). Higher lactate/albumin ratio was associated with an increased mortality in sepsis and septic shock patients (fixed-effects model; OR 1.49 (95% CI 1.37-1.62); p <0.001).Conclusions. High lactate/albumin ratio was associated with mortality in sepsis and septic shock patients. Thus, lactate/albumin ratio can be used as a predictor biomarker in predicting mortality for sepsis and septic shock patients.